SEKUEN PADA HEMPASAN GELOMBANG KARYA TAUFIK IKRAM JAMIL: KAJIAN TEORI STRUKTUR NARATIF SEYMOUR CHATMAN - H, Rosman (Jurnal Ilmu Budaya, 2009)
The research is entitled Hempasan Gelombang of Taufik Ikram Jamil: A Study of Narrative Structure of Seymore Chatman. The material object of this research is Hempasan Gelombang written by Taufik Ikram Jamil and the formal object is the narrative structure of Seymour Chatman. This research aims to describe narrative structure of Seymore Chatman in Hempasan Gelombang, by identifying units of the story, analyzing the level of core function and connecting function, analyzing level of action and analyzing level of narrative.